2021
DOI: 10.1111/1471-0528.16968
|View full text |Cite
|
Sign up to set email alerts
|

Asthma severity and impact on perinatal outcomes: an updated systematic review and meta‐analysis

Abstract: Background Large-scale studies exploring the associations of asthma severity, exacerbations and medication use with adverse perinatal outcomes have been published in recent years.Objectives To update evidence on the associations of asthma severity, exacerbations and medication use with the adverse perinatal outcomes of preterm delivery (PD), low birthweight (LBW) and small-for-gestational-age (SGA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…25 In the first trimester, corticosteroids may increase the risk of fetal orofacial cleft, 26 and when administered in the third trimester, associations with low birth weight and reduced head circumference of the baby have been noted. 27,28 On the other hand, the benefits of corticosteroids are considered more important than the rare side effects found in other diseases, for example, severe asthma, 29 or when fetal lung maturation must be accelerated in preterm deliveries. 30 No effect of corticosteroid treatment on the remission of Bell's palsy in pregnant women was seen.…”
Section: Discussionmentioning
confidence: 99%
“…25 In the first trimester, corticosteroids may increase the risk of fetal orofacial cleft, 26 and when administered in the third trimester, associations with low birth weight and reduced head circumference of the baby have been noted. 27,28 On the other hand, the benefits of corticosteroids are considered more important than the rare side effects found in other diseases, for example, severe asthma, 29 or when fetal lung maturation must be accelerated in preterm deliveries. 30 No effect of corticosteroid treatment on the remission of Bell's palsy in pregnant women was seen.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggests that degree of asthma severity is associated with poorer outcomes for the offspring. A meta-analysis by Xu and colleagues found that pregnant women with an asthma exacerbation had an increased risk of delivering low birth weight (LBW) babies and small-for-gestational age (SGA) babies, compared with pregnant women with asthma but without an exacerbation [pooled adjusted odds ratio (OR): 1.15, 95% CI 1.02–1.29 for LBW; number of studies with adjusted OR: 3; I 2 = 0%] (pooled adjusted OR: 1.13, 95% CI 1.04–1.23 for SGA; number of studies with adjusted OR: 4; I 2 = 0%) and compared with pregnant women without asthma [23 ▪▪ ].…”
Section: Management Of Severe Asthma In Pregnancymentioning
confidence: 99%
“…Asthma during pregnancy is a significant public health issue because it is one of the most potentially serious medical problems to complicate pregnancy. Studies have shown that having asthma during pregnancy puts both mother and baby at risk for complications 1 .…”
Section: Introductionmentioning
confidence: 99%